2004
DOI: 10.1002/joc.1064
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation as an urban climate control in the subtropical city of Gaborone, Botswana

Abstract: The influence of vegetation on the urban climate was studied in the subtropical city Gaborone, the rapidly expanding capital of Botswana with approximately 200 000 inhabitants. Temperature records from an urban and a rural station were analysed for the period 1985-96. In an attempt to explain possible seasonal change in vegetation, NOAA satellite normalized difference vegetation index imagery was analysed. The present urban influence was investigated with temperature loggers at selected urban and rural sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(112 citation statements)
references
References 17 publications
6
93
0
5
Order By: Relevance
“…an increase in specific humidity around sunset and intensive cooling has been reported from vegetated urban areas in Gaborone, Botswana by Jonsson (2004). He suggested that the increase in specific humidity was a result of evapotranspiration enhanced by irrigation.…”
Section: Phase 1 -Site-dependent Coolingmentioning
confidence: 93%
See 3 more Smart Citations
“…an increase in specific humidity around sunset and intensive cooling has been reported from vegetated urban areas in Gaborone, Botswana by Jonsson (2004). He suggested that the increase in specific humidity was a result of evapotranspiration enhanced by irrigation.…”
Section: Phase 1 -Site-dependent Coolingmentioning
confidence: 93%
“…Many (sub)tropical cities show a clear seasonal difference in NUHI intensities, with 0.5-3 K lower intensity during the wet season compared to the dry season (Okoola, 1990;Jauregui et al, 1992;Jauregui, 1997;Robaa, 2003;Jonsson, 2004;Chow and Roth, 2006;Roth, 2007;Balogun et al, 2009). The lower NUHI intensities during the wet season are explained by the higher amount of cloud cover, but also by thermal admittance due to increased soil-water (Jauregui, 1997;Jonsson, 2004;Jonsson and Lindqvist, 2005;Roth, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available work is primarily concerned with the influence of the built form (geometry, height-to-width of street canyons) to promote ventilation, building materials and colour as means to reduce the absorption of solar radiation and storage of heat as well as the role of vegetation for shading and evaporative cooling to moderate the thermal and moisture climate. Studies were conducted in the following climate types and cities: (1) equatorial wet Colombo (Emmanuel, 2003(Emmanuel, , 2005aEmmanuel and Johansson, 2006), Sao Paolo (Ribeiro, 2005) and Singapore (Wong et al, 2003;Wong and Yu, 2005;Chen and Wong, 2006), (2) tropical wet/dry Belo Horizonte (Sad de Assis and Frota, 1999), (3) tropical highland Mexico City and (4) subtropical dry San Juan, Argentina (Papparelli et al, 1996), Gaborone (Jonsson, 2004), Fez, Marocco (Johansson, 2006), various cities in Algeria (Ali-Toudert et al, 2005;Ali-Toudert and Mayer, 2006), Dimona, Israel (Pearlmutter et al, 2007a) and various settlements in the Negev desert of Israel which are reviewed by Pearlmutter et al (2007b) with special attention given to the relationship between urban geometry and thermal stress.…”
Section: Urban Design and Human Comfortmentioning
confidence: 99%